Localization of UvrA and Effect of DNA Damage on the Chromosome of Bacillus subtilis - Smith, Bradley T. (American Society for Microbiology, 2002)
We found that the nucleotide excision repair protein UvrA, which is involved in DNA damage recognition, localizes to the entire chromosome both before and after damage in living Bacillus subtilis cells. We suggest that the UvrA(2)B damage recognition complex is constantly scanning the genome, searching for lesions in the DNA. We also found that DNA damage induces a dramatic reconfiguration of the chromosome such that it no longer fills the entire cell as it does during normal growth. This reconfiguration is reversible after low doses of damage and is dependent on the damage-induced SOS response. We suggest that this reconfiguration of the chromosome after damage may be either a reflection of ongoing DNA repair or an active mechanism to protect the cell’s genome. Similar observations have been made in Escherichia coli, indicating that the alteration of chromosome structure after DNA damage may be a widespread phenomenon.